2012
DOI: 10.4236/ojas.2012.22010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic powder on performance and lipid profile of broilers

Abstract: This experiment was conducted to investigate the effect of feeding garlic powder (GP) on the performance, digestibility, digestive organs, carcass cuts and lipid profile of broilers. A total of 270 day-old Cobb-500 chicks were used in the experiment. Birds were partitioned into three experimental groups of 90 birds in each. Each treatment was composed of 6 replicates with 15 birds in each. The control group was fed with a commercial starter and finisher diet. The second and third groups were supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
46
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 26 publications
(40 reference statements)
13
46
3
Order By: Relevance
“…Similar findings with respect to increased FCR were reported by earlier researchers [9,10,12,18,20,21]. In contrary to findings of this study, some authors observed that the supplementation of garlic and neem leaves had no significant (p>0.05) effect FCR [14,16,[22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 56%
“…Similar findings with respect to increased FCR were reported by earlier researchers [9,10,12,18,20,21]. In contrary to findings of this study, some authors observed that the supplementation of garlic and neem leaves had no significant (p>0.05) effect FCR [14,16,[22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, it contains a varying amount of allicin, vitamins (vitamin С, thiamine, riboflavin and niacin), selenium and potassium (Anonymous, 2014a). The dietary supplementation of garlic powder in chickens was found to be beneficial for growth performance (Raeesi et al, 2010;Issa and Omar, 2012;Elagib et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it contains a varying amount of allicin, vitamins (vitamin С, thiamine, riboflavin and niacin), selenium and potassium (Anonymous, 2014a). The dietary supplementation of garlic powder in chickens was found to be beneficial for growth performance (Raeesi et al, 2010;Issa and Omar, 2012;Elagib et al, 2013).The combination of probiotics with substances with prebiotic activity improves the effect of the former due to creation of more favorable environment for replication of probiotic bacteria in poultry gut. This study was aimed at evaluating the growth performance of male classic broiler chickens whose feed was supplemented with either garlic powder, probiotics or both.…”
mentioning
confidence: 99%
“…Glutathione peroxidase is one of the most important antioxidants in the body and of significant importance for the digestive tract, gastrointestinal mucosa and the liver (Bengmark, 1998). Thus, further exploration of such morphological changes in gastrointestinal tissues, which are supposedly caused by plant feed additives, could provide further information on possible benefits to the digestive tract (Windisch et al, 2008;Issa et al, 2012). The objective of this experiment was to determine the effects of dietary additive supplementation of M. oleifera leaf meal (MOLM) on digestive organ size, intestinal morphology and digesta pH of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%